Identifying the clonal relationship model of multifocal papillary thyroid carcinoma by whole genome sequencing. (28th June 2017) - Xia, Mao; Li, Hengyu; Ma, Qian; Yu, Dong; Li, Jing; Zhang, Yi; Sheng, Yuan; Guo, Yingjun
Abstract: Purpose: To evaluate the application of whole genome sequencing (WGS) in determining the inter-foci clonal relationship of multifocal papillary thyroid carcinoma (mPTC). Methods: After reviewing PTC patient profiles, 8 cancer foci and germline control samples from 3 mPTC patients were analyzed by WGS. Single nucleotide variations (SNVs), copy number variation (CNV), structural variation and mutational signature were examined. Results: The multifocality rate of PTC was 35.1% and mPTC were shown to have larger primary tumor diameter, higher rate of lymph node metastasis and less number of accompanying non-cancerous lesions than single PTC in one or both gender groups. Out of the 8 cancer foci, 5 foci were identified as clonal-independent model with the rest 3 foci as clonal-derived model according to exonic SNVs spectrum. Non-exonic mutations provided compelling evidence at the genome-wide level for the classification. Specific CNV and 12 mutational signatures were also identified. Conclusions: WGS could be an impressive tool in clonal relationship determination of PTC by providing a panoramic view of genome-wide somatic mutations. The substantial sequencing data provided additional information that could help studying the mechanism of carcinogenesis. Highlights: The incidence rate of multifocality reached 35% in our cohort consisting of 920 PTC patients. Multifocal PTC presented unique clinicopathological characteristics including higher preference for lymph node metastasis. Both clonal-independent and clonal-derived model were identified in the 8 cancer foci studied. Non-exonic mutations could play a critical role in clonal relationship analysis. Whole genome sequencing additionally offered crucial information about the molecular genetic characteristics of cancer.